The Regulation of Banks and Financial Institutions - Ajayi, Olukonyinsola (Nigeria: Greyhouse African Professional Resources Development Project, 1991)
The book shed more light on the numerous provisions of the banking statutes, and provides a good understanding of the regulation of banks and financial institutions.
Includes index.
rua 26/08/16
Loans
Keywords: Bank regulation; Banking law; Financial Institutions - Law and Legislations; Nigeria